The Significance and Management of Incidental [18F]Fluorodeoxyglucose–Positron-Emission Tomography Uptake in the Thyroid Gland in Patients with Cancer - Eloy, J.A.; Brett, E.M.; Fatterpekar, G.M.; Kostakoglu, L.; Som, P.M.; Desai, S.C.; Genden, E.M. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Incidental positron-emission tomography (PET) uptake in the thyroid bed represents a diagnostic dilemma. Currently, there is no consensus regarding the significance of this finding or the most appropriate approach to management. The purpose of this study was to determine the significance of incidental fluorodeoxyglucose (FDG) uptake in the thyroid gland on [18F]FDG–positron-emission tomography (FDG-PET/CT) in patients being initially staged for lymphomas and/or cancers other than of thyroid origin.MATERIALS AND METHODS: A retrospective review was conducted on patients who were incidentally found to have focal FDG uptake in the thyroid bed on initial staging for cancer. Patient records were assessed for age, sex, clinical presentation, standard uptake values (SUVmax), on FDG-PET/CT, and CT findings in those patients undergoing FDG-PET/CT, fine-needle aspiration (FNA) cytology, and surgical pathologic examination.RESULTS: Thirty patients were identified with incidental FDG-PET uptake in the thyroid bed from 630 studies performed for evaluation of cancer between March 2004 and June 2006. Complete records were available for 18 patients (6 men, 12 women). Five (27.8%) of 18 patients with incidental focal FDG-PET/CT uptake in the thyroid gland demonstrated papillary thyroid carcinoma on final pathologic findings. The mean and SD of SUVmax was 3.0 ± 1.8 (range, 1.1–7.4) overall, 2.9 ± 1.6 (range, 1.1–6.8) in the patients without malignant growth, and 3.4 ± 2.6 (range, 1.1–7.4) in the 5 patients with papillary thyroid carcinoma. No statistical difference in SUVmax was noted between patients with papillary thyroid carcinoma and patients with benign pathologic findings (P = .63).CONCLUSIONS: Incidental FDG-PET uptake in the thyroid gland in patients with cancer of nonthyroidal origin is associated with a 27.8% risk for well-differentiated thyroid carcinoma; however, there seems to be no correlation between intensity of FDG uptake and the risk for a malignant process.